ATM broadband network multilevel control - Kan, Siew Leong. (2008)
A new policing method, leaky bucket scheme, is proposed to monitor and control user traffic in an ATM network. By simulation, the effect of this new multilevel control leaky bucket scheme is studied, evaluated and compared to the conventional leaky bucket scheme in terms of average cell inter-departure time, cell delay, burstiness of traffic at the output of the leaky bucket and the potential cell loss rate when the spacing defined in the spacer and the token generation rate are changed.